Quality of Work Life and Organizational Commitment of Nurses Who Work at JCI Accredited Hospitals in Bangkok Area - มะโนวรรณ, ดวงสมร (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2018)
The purposes of the study were 1) to study the quality of work life and the organizational commitment of hospital nurses 2) To study the relationship between quality of life in work and organizational commitment of nurses 3) to study the quality of work life that influenced to the organizational commitment of hospital nurses. The samples consisted of 400 nurses who work at JCI accredited hospitals in Bangkok area. Data collected through the survey method by Quality of Work Life Questionnaire (QWL) and Organizational Commitment Questionnaire (OCQ). The Questionnaire was tested for quality and resulted in a reliability coefficient of 0.815. The data were analyzed by percentage, means, standard deviation, one-way analysis of variance, Pearson’s product moment correlation and multiple regression analysis. The results showed that the quality of working life of nurses was at a high level. There are the benefits to society, the workplace safety and good hygiene in the workplace, and the development of human capacity respectively. The organization’s commitment as perceived by employees was high in all aspects at 0.05 was statistically significant. And the research indicated that the elements of the quality of working life of adequate and fair compensation, the workplace safety and good hygiene, the good cooperation with colleagues, the work life balance, and the benefits to society have a positive influence in organizational commitment at 0.05 statistically significant levels.